Reducing the loss of velocity and power in women athletes via rest redistribution - Merrigan, J. J.; Tufano, J. J.; Oliver, J. M.; White, J. B.; Fields, J. B.; Jones, M. T. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To examine rest redistribution (RR) effects on back squat kinetics and kinematics in resistance-trained women. Methods: Twelve women from strength and college sports (5.0 [2.2] y training history) participated in the randomized crossover design study with 72 hours between sessions (3 total). Participants completed 4 sets of 10 repetitions using traditional sets (120-s interset rest) and RR (30-s intraset rest in the middle of each set; 90-s interset rest) with 70% of their 1-repetition maximum. Kinetics and kinematics were sampled via force plate and 4 linear position transducers. The greatest value of repetitions 1 to 3 (peak repetition) was used to calculate percentage loss, [(repetition 10-peak repetition)/(peak repetition)x100], and maintenance, {100-[(set mean-peak repetition)/(peak repetition)] × 100}, of velocity and power for each set. Repeated-measures analysis of variance was used for analyses (P< .05). Results: Mean and peak force did not differ between conditions. A condition × repetition interaction existed for peak power (P=.049) but not for peak velocity (P=.110). Peak power was greater in repetitions 7 to 9 (P<.05; d1.12-1.27) during RR. The percentage loss of velocity (95% confidence interval, -0.22% to -7.22%; P=.039) and power (95% confidence interval, -1.53% to -7.87%; P=.008) were reduced in RR. Mean velocity maintenance of sets 3 (P=.036; d=1.90) and 4 (P=.015; d=2.30) and mean power maintenance of set 4 (P=.006; d=2.65) were greater in RR. Conclusion: By redistributing a portion of long interset rest into the middle of a set, velocity and power were better maintained. Therefore, redistributing rest may be beneficial for reducing fatigue in resistance-trained women.